Simulating green house gas emissions of constructed wetland treatment systems saturated with coal-fired powerplant effluent - Wellemeyer, Thomas B. (My University, 2015)
Constructed Wetland Treatment Systems (CWTS) are demonstrated to effectively trap carbon and methane emissions (Mitsch et. al, 2012). However, limited research has been conducted on the use of CWTS to remediate flue gas desulphurization (FGD) effluent. Based upon the high sulfur content of coal-fired powerplant effluent, it is likely that sulfate-reducing bacteria will be prevalent and reduce methanogenisis. In this project, six bioretention cells were built to model the CWTS at Jeffery Energy Center, and they will eventually be saturated with effluent so that the biological activity can be assessed by means of gas chromatography. Gas samples will be drawn through ports throughout the height of the cell to determine variability of greenhouse has production. Methane and carbon dioxide will be measured in initial trials to analyze the carbon sink potential of CWTS for FGD effluent.